PENERAPAN PERENCANAAN PAJAK PENGHASILAN PASAL 21 SEBAGAI STRATEGI PENGHEMATAN PEMBAYARAN PAJAK PADA YAYASAN KURNIA - Rioni, Yunita Sari; Saraswati, Dwi; Junawan, Junawan (JURNAL PERPAJAKAN, 2024)
Tax planning is one of the ways that taxpayers can utilize in managing their business or income taxation, but it should be noted that the intended tax planning is tax planning without violating the constitution or applicable taxation laws. Tax Planning is a capacity that is owned by the Taxpayer (WP) to arrange financial activities in order to get a minimum tax expenditure (burden). Theoretically, tax planning is known as effective tax planning, which is a taxpayer trying to get tax savings through tax avoidance procedures systematically in accordance with the provisions of the Taxation Law. An appropriate tax planning will produce a minimal tax burden that is the result of tax savings and / or tax avoidance that can be received by the tax authorities and not at all due to tax smuggling that cannot be accepted by the tax authorities and will not be tolerated (Ruchjana, 2008) . Good planning requires taxpayers to follow and know the latest developments in taxation regulations (Gloritho, 2009).